HPLC/MS-MS Identification of Oak Quercus aegilops Root Tannins - Ayed S. Amr; Mousa N. Ahmad; Jalal A. Zahra; Mai A. Abdullah (Journal of Chemistry)
Tannins are natural polyphenolic compounds widely distributed in the plant kingdom in the leaves, bark, fruits, and other parts. They have various biological functions in humans and animals and are used mainly in the pharmaceutical and cosmetic industries. The aim of this work was to isolate, extract, purify, and identify the tannins from the root bark of a common oak tree (Quercus aegilops L.) in Jordan and around the Mediterranean. The results showed that at least one form of ellagitannin (ellagic acid ester), quercitrin, afzelechin, valoneic acid, trigalloyl glucose, and catechin was identified in addition to two unidentified compounds. Results of this work can help in developing an ESI MS/MS search library for the constituents of the tannins of oak (Quercus aegilops L.) root bark.